The resumption of the land (tekoharã) in Mato Grosso do Sul and facing the logic of financialization of the territory - Souza, José Gilberto de; Mizusaki, Márcia Yukari (GEOUSP Espaço e Tempo (Online), 2022)
The work focuses its analysis on private property, on the agricultural and financial dynamics of the land in Mato Grosso do Sul, based on the premise that the State has been the main legitimizing agent of the process of appropriation of the lands of the original towns that compete with the forms of struggle for the recovery of their traditional territories. The work begins with a brief ethno-historical-geographic contextualization of the Kaiowá and Guaraní with respect to the constitution of private land ownership, and the incorporation of this fraction of space in the national State and how territorial determinations of this social conflict are analyzed, understanding them as the state and movement of the socio-spatial practices of the subjects in the consolidation of hegemony and resistance projects. It is concluded that in opposition to the form of value, the centrality of the territorial determinations of agribusiness, the resumption of land (tekoharã) is generated, which represents the confrontation, the resistance, of the native peoples to the genocidal project of the capital-State.